Int Arch Orthop Surg 2019
DOI: 10.23937/iaos-2017/1710006
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Outcome of Femoral Fractures Treated in a Regional Trauma Centre in South South, Nigeria

Abstract: The pattern of presentation of femoral fractures varies with age of the patient, cause, and severity of the injury, and the location of the fracture on the femur [4,5]. In young persons, fractures of the femur are generally caused by high-energy forces and are often associated with multisystem injury. However, in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 25 publications
4
9
1
Order By: Relevance
“…Road traffic collisions (65%) remain the most common injury mechanism followed by fall from height in our series. These findings agree with earlier studies which also reported high impact trauma, mainly road traffic crashes as the commonest cause of femur fractures [ 2 , 21 ]. Furthermore, traffic-related injuries were more evident among young individuals of 14–30 years of age, who represent the most active age group of young individuals, usually involved in over-speeding and reckless driving.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Road traffic collisions (65%) remain the most common injury mechanism followed by fall from height in our series. These findings agree with earlier studies which also reported high impact trauma, mainly road traffic crashes as the commonest cause of femur fractures [ 2 , 21 ]. Furthermore, traffic-related injuries were more evident among young individuals of 14–30 years of age, who represent the most active age group of young individuals, usually involved in over-speeding and reckless driving.…”
Section: Discussionsupporting
confidence: 93%
“…There are several key features of the current analysis. It was identified that the proportion of traumatic femur fracture cases managed at our center was 11%, which is in agreement with an earlier study that reported similar rates of femoral fractures treated at a regional trauma center in South Nigeria [ 21 ]. The results of our study showed a preponderance of male gender (89.4%) and young age (mean: 30 years), which is in line with an earlier study from Saudi Arabia, but the mean age was a slightly lower than the mean of 33 years reported there [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Diaphyseal femur fractures are preferably treated with intramedullary nailing which helps to attain appropriate bone alignment, quicker bone healing that allows early mobilization and lower rate of complications [14]. An earlier study from our center observed an association between early intramedullary nailing (within 12 h of injury) with fewer hospital complications and shorter length of hospital stay [15]. Similarly, Harvin et al [13] reported an independently association between early intramedullary nailing (within 24 hours) for femur xation with lower rate of pulmonary complications.…”
Section: Introductionmentioning
confidence: 99%